Mesenchymal Stem Cells for Tissue Engineering - Yenny Yustisia (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Mesenchymal stem cells (MSCs) have generated a promise as a potential source of cells for tissue engineering application due to their instrinsic ability to self-renew and differentiate into functional cell types. With their ability to differentiate into multiple cell phenotypes, mesenchymal stem cells offer the potential to regenerate entire tissue from a single cell source. Recent studies have demonstrated that MSCs were successfully used for bone repair, cartilage repair and soft tissue repair. This paper briefly outlines the biological characteristics of Mesenchymal stem cell and its application in tissue engineering field.